Pinpointing Mechanisms of a Mechanistic Treatment: Dissociable Roles for Overt and Covert Attentional Processes in Acute and Long-Term Outcomes Following Attention-Bias Modification. (September 2019) - Price, Rebecca B.; Woody, Mary L.; Panny, Benjamin; Siegle, Greg J.
Biased patterns of attention toward threat are implicated as key mechanisms in anxiety that can be modified through automated intervention (attention-bias modification; ABM). Intervention refinement and personalized dissemination efforts are substantially hindered by gaps in understanding the precise attentional components that underlie ABM's effects on symptoms—particularly with respect to longer-term outcomes. Seventy adults with transdiagnostic anxiety were randomized to receive eight sessions of active ABM ( n = 49) or sham training ( n = 21). Reaction time and eye-tracking data, collected at baseline, posttraining, and 1-month follow-up, dissociated multiple core attentional processes spanning overt and covert processes of engagement and disengagement. Self-reported symptoms were collected out to 1-year follow-up. Covert disengagement bias was specifically reduced by ABM, unlike all other indices. Overt disengagement bias at baseline predicted acute post-ABM outcomes, whereas covert engagement bias was nonspecifically predictive of symptom trajectories out to 1-year follow-up. Results suggest unique and dissociable roles for each discrete mechanism.